2013
DOI: 10.2337/dc12-1743
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control and Blood Glucose Monitoring Over Time in a Sample of Young Australians With Type 1 Diabetes

Abstract: OBJECTIVETo determine whether personality traits (conscientiousness, agreeableness, emotional regulation, extraversion, and openness to experience) are associated with glycemic control and blood glucose monitoring behavior, and change or stability of these outcomes over time, in young people with type 1 diabetes.RESEARCH DESIGN AND METHODSA 3-year longitudinal study was conducted using data from 142 individuals with type 1 diabetes, 8–19 years of age. Personality was assessed at baseline using the Five-Factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 17 publications
2
30
3
Order By: Relevance
“…Conversely, in a sample of Type 2 diabetic participants, SzymborskaKajanek et al (2006) found higher HbA1c was associated with higher neuroticism, lower agreeableness (the tendency to be altruistic and cooperative), and lower conscientiousness (the tendency to be responsible and organized). Waller et al (2013) found higher conscientiousness and agreeableness were associated with more stable HbA1c over a 3-year period for participants with Type 1 diabetes. Finally, Skinner et al (2014) found no association with HbA1c and any of the five personality factors for those with Type 2 diabetes.…”
Section: Five-factor Model Of Personality and Diabetesmentioning
confidence: 95%
“…Conversely, in a sample of Type 2 diabetic participants, SzymborskaKajanek et al (2006) found higher HbA1c was associated with higher neuroticism, lower agreeableness (the tendency to be altruistic and cooperative), and lower conscientiousness (the tendency to be responsible and organized). Waller et al (2013) found higher conscientiousness and agreeableness were associated with more stable HbA1c over a 3-year period for participants with Type 1 diabetes. Finally, Skinner et al (2014) found no association with HbA1c and any of the five personality factors for those with Type 2 diabetes.…”
Section: Five-factor Model Of Personality and Diabetesmentioning
confidence: 95%
“…Negative relationships have been found between adherence behavior and neuroticism [32,35] and extraversion [28]. Low or high neuroticism scores in patients with type 1 diabetes showed worse glycaemic control, suggesting a non-linear relationship may exist between these variables [29]. Conscientiousness, agreeableness and extraversion have been shown to positively correlate with self-efficacy [36,37], whilst a negative relationship between neuroticism and self-efficacy has been found [36,38].…”
Section: Introductionmentioning
confidence: 95%
“…For example, the traits conscientiousness [29][30][31]33,34] and agreeableness [35] have been found to have positive associations with adherence to medication regimens and diabetic glycaemic control [29]. Conscientiousness also predicted HIV disease progression and patients' coping [31].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Two studies (Waller et al, 2013;Wheeler, Wagaman, & McCord, 2012) investigated the relationships between self-management and the five personality factors of conscientiousness, openness to experience, extraversion, agreeableness and neuroticism/emotional regulation. Strong correlations were observed for four of the personality factors (Wheeler et al, 2012): higher levels of conscientiousness with greater adherence to insulin administration and dietary advice; higher levels of agreeableness with greater adherence to insulin administration; greater neuroticism with lower levels of insulin adherence; and higher levels of extraversion with greater adherence to exercise.…”
Section: Running Head: Psychological Factors and Adolescent Diabetes 15mentioning
confidence: 99%